Essential Care for Every Baby: improving compliance with newborn care practices in rural Nicaragua - Krystle Perez; Jacquelyn Patterson; Jessica Hinshaw; Carlos Escobar; David Parajon; Laura Parajon; Carl Bose (BMC, 2018)
Abstract Background Neonatal mortality comprises an increasing proportion of childhood deaths in the developing world. Essential newborn care practices as recommended by the WHO may improve neonatal outcomes in resource limited settings. Our objective was to pilot a Helping Babies Breathe and Essential Care for Every Baby (HBB and ECEB) implementation package using HBB-ECEB training combined with supportive supervision in rural Nicaragua. Methods We employed an HBB-ECEB implementation package in El Ayote and Santo Domingo, two rural municipalities in Nicaragua and used a pre- and post- data collection design for comparison. Following a period of pre-intervention data collection (June-August 2015), care providers were trained in HBB and ECEB using a train-the- trainer model. An external supportive supervisor monitored processes of care and collected data. Data on newborn care processes and short-term outcomes such as hypothermia were collected from facility medical records and analyzed using standard run charts. Home visits were used to determine breastfeeding rates at 7, 30 and 60 days. Results There were 480 institutional births during the study period (June 2015-June 2016). Following the HBB-ECEB implementation package, cord care improved (pre-intervention median 66%; post-intervention shift to ≥85%) and early skin-to-skin care improved (pre-intervention median 0%; post-intervention shift to ≥56%, with a high of 92% in June 2016). Rates of administration of ophthalmic ointment and vitamin K were high pre-intervention (median 97%) and remained high. Early initiation of breastfeeding increased with a pre-intervention median of 25% and post-intervention shift to ≥28%, with a peak of 81% in June 2016. Exclusive breastfeeding rates increased short-term but were not significantly different by 60-days of life (9% pre-intervention versus 21% post-intervention). Conclusions The implementation of the HBB-ECEB programs combined with supportive supervision improved the quality of care for newborns in terms of cord care, early skin-to-skin care and early initiation of breastfeeding. The rates of administration of ophthalmic ointment and vitamin K were high pre- intervention and remained high afterwards. These findings show that HBB-ECEB programs implemented with supportive supervision can improve quality of care for newborns.